Microfluidic Generation of Monodisperse Nanobubbles by Selective Gas Dissolution. Issue 20 (2nd April 2021) - Xu, Jiang; Salari, Alinaghi; Wang, Yanjie; He, Xiaolin; Kerr, Liam; Darbandi, Ali; de Leon, Al C.; Exner, Agata A.; Kolios, Michael C.; Yuen, Darren; Tsai, Scott S. H.
Abstract: Nanotechnology currently enables the fabrication of uniform solid nanoparticles and liquid nano‐emulsions, but not uniform gaseous nanobubbles (NBs). In this article, for the first time, a method based on microfluidics that directly produces monodisperse NBs is reported. Specifically, a two‐component gas mixture of water‐soluble nitrogen and water‐insoluble octafluoropropane as the gas phase are used in a microfluidic bubble generator. First, monodisperse microbubbles (MBs) with a classical microfluidic flow‐focusing junction is generated, then the MBs shrink down to ≈100 nm diameter, due to the dissolution of the water‐soluble components in the gas mixture. The degree of shrinkage is controlled by tuning the ratio of water‐soluble to water‐insoluble gas components. This technique maintains the monodispersity of the NBs, and enables precise control of the final NB size. It is found that the monodisperse NBs show better homogeneity than polydisperse NBs in in vitro ultrasound imaging experiments. Proof‐of‐concept in vivo kidney imaging is performed in live mice, demonstrating enhanced contrast using the monodisperse NBs. The NB monodispersity and imaging results make microfluidically generated NBs promising candidates as ultrasound contrast and molecular imaging agents. Abstract : For the first time, monodisperse nanobubbles (NBs) of a high throughput are generated directly via a microfluidic device. Microbubbles, containing a gas core of soluble and insoluble gas components, can shrink down to nanoscale in a precisely controlled manner. These monodisperse NBs exhibit enhanced contrast in vivo ultrasound imaging and can be potentially applied to other fields.